Election integrity and good governance (a case study of Iraq after 2005) (قضايا سياسية, 2024)
Fair elections are considered one of the most important foundations on which good governance is based. Fair elections lead to the existence of true democracy, and determine the fate of the state and the fate of democratic transformation and governance in it. If the elections are not characterized by integrity, they will be considered sham elections, but if the elections are free and fair, they will lead to achieving For good governance.